The Latest Clinical Advances in Thrombocytopenia - ten Cate, Hugo; Lammle, Bernhard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Platelets are critical elements in the blood stream, supporting hemostasis (defense against bleeding), as well as performing even more complex tasks within networks of biological (immunity) and pathophysiological processes, such as cancer and ischemia/reperfusion injury. Changes in the number (and function) of platelets may have a substantial impact on any of these processes. The "simple" finding of a reduced platelet count (thrombocytopenia) has a history (origin) and a consequence (e.g., bleeding). This book brings together international experts to provide an up-to-date overview of the impact of thrombocytopenia from a clinical perspective.